2011
DOI: 10.1103/physrevb.84.094123
|View full text |Cite
|
Sign up to set email alerts
|

Precursor dynamics in the ferroelectric phase transition of barium titanate single crystals studied by Brillouin light scattering

Abstract: The acoustic anomalies and precursor dynamics of high-quality barium titanate single crystals were investigated by Brillouin light scattering and the birefringence measurements in the paraelectric phase above the cubic-totetragonal ferroelectric phase transition temperature (T c ). Two elastic stiffness coefficients C 11 and C 44 , the related sound velocities, and their absorption coefficients were determined from T c to 400 • C for the first time. The longitudinal acoustic (LA) mode showed a substantial soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
92
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 39 publications
13
92
1
Order By: Relevance
“…9 Deviation degree ΔTcm from the Curie-Weiss law at the frequency of 100 kHz obtained for BT, BPT, BPTC(0.1 %) and BPTC(1 %) ceramics despite the fact that the remnant polarization is not measurable [37]. Brillouin light scattering studies [38,39] showed anomalous changes of acoustic phonons accompanied by the appearance of quasielastic central peak on approaching Tc in the paraelectric phase. Moreover, many theoretical works based on the first-principle calculations and polarizability model [40][41][42] have been done to explain the deviation from Curie-Weiss behavior due to the complex dynamics of the transition.…”
Section: Resultsmentioning
confidence: 99%
“…9 Deviation degree ΔTcm from the Curie-Weiss law at the frequency of 100 kHz obtained for BT, BPT, BPTC(0.1 %) and BPTC(1 %) ceramics despite the fact that the remnant polarization is not measurable [37]. Brillouin light scattering studies [38,39] showed anomalous changes of acoustic phonons accompanied by the appearance of quasielastic central peak on approaching Tc in the paraelectric phase. Moreover, many theoretical works based on the first-principle calculations and polarizability model [40][41][42] have been done to explain the deviation from Curie-Weiss behavior due to the complex dynamics of the transition.…”
Section: Resultsmentioning
confidence: 99%
“…We note that τ in KF-substituted BaTiO 3 , determined in the same way, obeys the critical slowing down, i.e., τ becomes larger and larger toward T C . [31][32][33] The differences in τ between PZN-xPT and KF-substituted BaTiO 3 should reflect the different growing processes of their PNRs, as discussed in Sec. III B.…”
Section: Polarization Relaxation Coupled With the La Phononmentioning
confidence: 99%
“…5,19,20,[31][32][33]39 From the macroscopic point of view, the difference between them is the appearance of inflexion points in ν B , , ε , and ε . For example, Fig.…”
Section: B Elastic Anomaly At T *mentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature evolution of this interdependence of the structural and polar soft mode could be responsible for non-classical dependences reported earlier. 22 Similar mechanism can be applicable to PZS. The question remains as to why both in the case of ferroelectric and antiferroelectric transitions this thermal hysteresis takes place.…”
Section: Discussionmentioning
confidence: 98%